VALIDATION OF INDONESIAN VERSION OF IPSS - Monoarfa, Richard Arie; Mochtar, Chaidir Arif (Indonesian Urological Association, 2014)
Objective: This study aims to validate the Indonesian version of International Prostate Symptom Score (IPSS)to ensure similar purpose and quality as the original version. Material & method: Validation and reliability of IPSS-Ina was performed on 174 subjects divided into 87 benign prostate hyperplasia(BPH) patients and 87 non-BPH subjects as a control group. A total of 33 patients in the BPH group then underwent TURP. Validation was assessed by correlating the IPSS score-Ina with a quality of life score (QoL). Reliability was tested by internal consistency with Cronbach α and test-retest trials. Sensitivity to changes in IPSS-Ina post-therapy was tested by comparing the mean IPSS before and after transurethral resection of the prostate (TURP) therapy. Results: Correlation between IPSS-Ina score with quality of life (QoL) was 0.85 (p <0.001),showing strong correlation.Results of Cronbach's α 0.93; while test-retest trials with the intraclass correlation coefficient (ICC) 0.99; which indicates a very good reliability. The mean initial IPSS-Ina (20.97 ± 4.4) with post-TURP (4.82 ± 1.77) differed significantly (p <0.001). Conclusion: IPSS-Ina proved excellent validation and reliability and was sensitive to symptomatic changeafter therapy. IPSS-Ina have the same goals and the quality of the original version.Keywords: International prostate symptom score, Indonesia, validation, reliability.